Activity of hemorrhagic metalloproteinase BaH-1 and myotoxin II from Bothrops asper snake venom on capillary endothelial cells in vitro - Lomonte, Bruno (1994)
In vivo, hemorrhagic toxins isolated from snake venoms cause a disorganization of the basal lamina of capillaries, with a concomitant degenerative process of endothelial cells. In this study we investigated the effects of BaH-1, a hemorrhagic metalloproteinase purified from the venom of Bothrops asper, on a murine endothelial cell line of capillary origin. A quantitative cytotoxicity assay based on the release of lactic dehydrogenase was utilized. BaH-1, despite its potent hemorrhagic activity, did not exert direct cytolytic activity on the endothelial cells, even at concentrations as high as 65 micrograms/ml. The only visible effect of BaH-1 on the cultured cells was a relatively slow, moderate detachment of cells, interpreted as a consequence of proteolytic degradation of extracellular matrix components. In contrast, myotoxin II, a lysine-49 phospholipase A2 from the same venom, was clearly cytotoxic to this cell type, albeit being devoid of hemorrhagic activity. These findings suggest that the ability of venom metalloproteinases to induce hemorrhage is not related to a direct cytotoxic action on endothelial cells, and that the rapid degenerative changes of endothelium observed in vivo are probably the result of an indirect mechanism.